Role of Calcium in Psoriatic Patients: A Hospital Based Study - Baral, Ekta; Shrestha, Rushma; Gurung, Sarita (Journal of Bharatpur Hospital, 2025)
Background: Psoriasis is a common chronic inflammatory skin disease characterized by erythematous papules and plaques with silvery scales. The hyper proliferation and keratinocyte differentiation in psoriasis is controlled by calcium inside the cells and disturbance in the metabolism of calcium has been observed in cases with psoriasis. The aim of this study was to find out the prevalence of deranged serum calcium in patients with psoriasis. Methods: A cross-sectional study was conducted in the Department of Dermatology, Bir Hospital from June 2019 to December 2020. Any patient presenting at dermatology OPD above 16 years of age with psoriasis were taken as cases. Age and gender matched patients with skin disease other than psoriasis were taken as controls. Determination of serum calcium level was done by fully automated random-access clinical chemistry analyzer Erba Manheim XL-300 in Biochemistry lab, Bir Hospital. The study was approved by the institutional review board. A p-value of <0.05 was considered statistically significant. Results: Out of 51 cases and 51 controls, low serum calcium level was found in 15(29.41%) of psoriasis patients and 12(23.53%) of the controls. This showed that hypocalcemia was observed more in psoriasis patients than the controls. However, the difference was not statistically significant (p=0.327). Conclusions: This study showed that hypocalcemia was observed more frequently in cases of psoriasis as compared to controls. However, the finding was not statistically significant.